Conservation in a Region of Political Instability: Bwindi Impenetrable Forest, Uganda - Hamilton, A.; Cunningham, A.; Byarugaba, D.; Kayanja, F. (Conservation Biology, 2000)
Bwindi Impenetrable is the most important forest in Uganda for conservation of biodiversity. It contains over half the world’s mountain gorillas. It is surrounded by densely populated agricultural land and lies within a region of political instability. Gazetted as a forest reserve in 1932, little forest now remains outside its boundaries. Transformation of nearby communal swampland to farmland, much owned by a few individuals, shows the probable fate of Bwindi if it had not been declared a protected area. Widespread illegal logging and other activities were among reasons why the status of the forest was raised to national park in 1991. This resulted in local resentment, fed by inadequate consultation and concern about the local people’s loss of access to resources. Fires were set in the forest and threats made against the gorillas. Three schemes to provide benefits from the existence of the forest to communities and involve them in park management were then instituted: agreements allowing controlled harvesting of resources in the park, receipt of some revenue from tourism, and establishment of a trust fund partly for community development. Tension between people and park has been reduced. This case demonstrates the importance of protected areas and community involvement in such circumstances. Community support is especially critical, as here, when resources available to park managers are limited and political instability endemic.
Keywords: Conservation; Political Instability; Bwindi Impenetrable Forest; Uganda